Automatic assembly design project 1968/9: report of assembly analysis and coordination committee - Shaw, C. R. (College of Aeronautics, 1969)
The present assembly method and component parts of a chosen product are analysed. The design of components is investigated, and a workstation sequence is proposed based upon the modified components. A pick-and-place head is designed, versatility being the main design criterion. A functional check mechanism is designed.